Drug utilization studies from secondary databases in latent tuberculosis: a scoping review protocol - Luiz Villarinho MENDES; Juliana Villar GUIMARÃES; Rondineli Mendes SILVA; Claudia Garcia OSORIO- (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2024)
This article introduces a protocol for a scoping review that aims to map and synthesize Drug utilization studies from secondary databases in latent tuberculosis The protocol is intended to document the processes involved in the methodological planning and execution of a scoping review guided by Joanna Briggs Institute guidelines and developed using the 2015 PRISMA-Protocols (PRISMA-P) checklist. The PCC strategy (population, concept and context) systematized the search for studies published in Pubmed, Scopus, BVS, Embase and Web of Science from January 2015 to December 2022. The selection of articles will be carried out in two steps (titles and abstracts, followed by the assessment of the full text of the articles), by two independent reviewers, with the resolution of disagreements by a third reviewer. The results will be analyzed qualitatively/quantitatively and will be organized by themes. The checklist present in the Preferred Reporting Items for Systematic Reviews and Meta-Analysis extension for Scoping Reviews (PRISMA-ScR) will be used to guide the final review report. We hope that this scoping review will shed light on Drug Utilization Research in the field of latent tuberculosis, which is still understudied, especially in Brazil.